Learning Morality from Handicapped Children - Hauerwas, Stanley (The Hastings Center report, 1980)
Book reviewed in this article: Families Against Society: A Study of Reactions to Chidren with Birth Defects. By Rosalyn Benjamin Darling The Unexpected Minority: Handicapped Children in America. By John Gliedman and William Roth